2011
DOI: 10.1074/jbc.m111.220996
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic, Kinetic, and Spectroscopic Study of the First Ligninolytic Peroxidase Presenting a Catalytic Tyrosine

Abstract: Trametes cervina lignin peroxidase (LiP) is a unique enzyme lacking the catalytic tryptophan strictly conserved in all other LiPs and versatile peroxidases (more than 30 sequences available). Recombinant T. cervina LiP and site-directed variants were investigated by crystallographic, kinetic, and spectroscopic techniques. The crystal structure shows three substrate oxidation site candidates involving His-170, Asp-146, and Tyr-181. Steady-state kinetics for oxidation of veratryl alcohol (the typical LiP substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 52 publications
2
49
0
Order By: Relevance
“…Previous work showing that LiP can bind to lignin favors this second view (69). Moreover, our observation that the C. subvermispora LiPs are as effective as P. chrysosporium LiPH8 at oxidizing the bulky substrate ferrocytochrome c (46,70) is consistent with our finding that these enzymes all exhibit similar activities on synthetic lignin.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous work showing that LiP can bind to lignin favors this second view (69). Moreover, our observation that the C. subvermispora LiPs are as effective as P. chrysosporium LiPH8 at oxidizing the bulky substrate ferrocytochrome c (46,70) is consistent with our finding that these enzymes all exhibit similar activities on synthetic lignin.…”
Section: Discussionsupporting
confidence: 82%
“…8), which in the two C. subvermispora peroxidases (118677 and 99382) is closer Table S1 for details) include five MnP-long enzymes (*) that could be classified as extra long MnPs (60) and two LiP-type enzymes (**) representing LiP/VP transition stages. Additionally, MnP-atypical corresponds to a MnP type with only two acidic residues at the oxidation site (as found in the Stereum hirsutum genome), TC-LiP corresponds to the unique LiP from Trametes cervina (46), and GP corresponds to generic peroxidases. See Ruiz-Dueñas and Martínez (29) for references of class II basidiomycete peroxidases (from GenBank TM and genomes).…”
Section: Discussionmentioning
confidence: 99%
“…Trp-171 mutants (W171F, W171S) were shown to be completely inactive, confirming Trp-171 as the peripheral substrate oxidation site (44,45) for substrates like veratryl alcohol. In a similar way, a tyrosine on the enzyme surface acts as the substrate interaction site in lignin peroxidase from Trametes cervina (26).…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxyl group Tyr-337 forms a strong hydrogen bond of 2.6 Å with the carboxylate of Glu-354. It has been reported that acidic side chains in the vicinity of a tryptophan or a tyrosine stabilize an emerging radical cation (26,47,48). Alignments with other DyPs show that Tyr-337 is a conserved residue in fungal as well as bacterial DyPs and the related enzymes TyrA from Shewanella oneidensis and EfeB from Escherichia coli but is missing in Cld-like proteins (5).…”
Section: Resultsmentioning
confidence: 99%
“…Ligninolytic peroxidases oxidize lignin polymer and xenobiotic dyes at an exposed protein radical, mainly a Trp residue [25][26][27][28] . An exception is represented by Trametopsis cervina LiP that uses an exposed Tyr as the catalytic site, but it requires the formation of a reactive adduct with veratryl alcohol 29 . This latter is the only case, to our knowledge, where a Tyr is involved in peroxidase catalysis.…”
Section: Introductionmentioning
confidence: 99%